Differentiation and identification of fungi by ATR-FTIR method in a leather collection relating back to Seljuk period - Mohsen Mohammadi Achachluei; Hosseyn Ahmadi; Alireza Koochakzaei (Biological Journal of Microorganism, 2013)
Introduction: Biodegradation is one of the main degrading factors of leather artifacts. Determination of fungi and other microorganisms has vital importance for conservation of valuable objects made from organic materials. Usual classic techniques for identification of pathogens and fungi have some difficulties, but FTIR spectroscopy has been introduced as useful technique for characterization and determination of microorganisms. Materials and methods: In this study, historic leathers were related to the Seljuk period. The leathers were sampled in laboratory and fungi were cultivated in SDA medium. Genuses of fungi were identified according to macroscopic, microscopic and morphologic characteristics. Microorganisms were analyzed by ATR-FTIR spectrometer and differences of spectral properties were assessed. Spectral properties were assessed according to form and absorption region of peaks. Cluster analysis was used for evaluation of different regions and areas on the measured spectra.Results: Results showed the presence of Penicillium sp. (9 samples, 33.3%), Aspergillus sp. (5 samples, 18.5%), Cladosporium sp. (4 samples, 14.8%), Rhizoctonia sp. (2 samples, 7.4%), Trichophyton sp. (1 sample, 3.7%) and also one sample of yeast (3.7%). Two species of fungi remained unidentified (7.4%) and there was not any growth in 3 samples (11.1%). Spectral properties indicated to structural differences between microorganisms (fungi, yeast, bacteria). It showed characteristics of fungi genus and species in some cases.Discussion and conclusion: Active fungi induce decomposition, hydrolysis and decay of leather and its vegetable tannins. The decay leads to aesthetic change and health problems. Therefore, it is necessary to remove of fungi and appropriate treatment of leather artifacts. Application of ATR-FTIR spectroscopy had good results for identification of fungi, yeast and bacteria. Assessments showed the potential of ATR-FTIR spectroscopy for easy and rapid discrimination between microorganisms and specially fungi genus and species in some cases. This study indicated the possibility of developing FTIR–ATR spectroscopy as a reliable method for rapid identification of fungal pathogens. Advantages of the method showed that it was an appropriate technique for fungi evaluation in large scale. IR spectroscopy could help in identification and classification of fungi. Combining the advantages of FTIR spectroscopy with other used routine techniques, might improve the efficiency of fungal classification and identification. Chemical composition of the samples can be simultaneously analyzed. Chemical analysis by FTIR spectroscopy results to better understanding of fungi growth and complex chemical processes during fungal development and substrate degradation.